Bioprocessing Strategies For Lipopeptide Biosurfactant Production In A Submerged Fermentation Of Streptomyces Sp. PBD-410L Using Palm Oil As Carbon Source - Zambry, Nor Syafirah (2020)
Biosurfactant is a biologically-derived surfactant, produced by fermentation of a heterogeneous group of living cells. Streptomyces sp. can be an appropriate candidate for a safe and industrially viable microbe for biosurfactants due to their non- pathogenicity to human. The study on the improvement of biosurfactant production through manipulation of bioprocessing strategies in a stirred-tank bioreactor (STR) particularly on this filamentous bacterium is very limited. This study is a requisite in gaining expertise and experience towards the production of mass production of biosurfactant in industrial applications.